Production of cellulases and xylanase by Aspergillus fumigatus SK1 using untreated oil palm trunk through solid state fermentation - Ang, Siow Kuang; Mohamad, Shaza Eva; Yahya, Adibah; Abd. Aziz, Suraini; Md Salleh, Madihah (Elsevier, 2013)
Direct utilization of untreated oil palm trunk (OPT) for cellulases and xylanase production by Aspergillus fumigatus SK1 was conducted under solid-state fermentation (SSF). The highest activities of extracellular cellulases and xylanases were produced at 80% moisture level, initial pH 5.0, 1 × 108 spore/g (inoculum) with 125 μm of OPT as sole carbon source. The cellulases and xylanase activities obtained were 54.27, 3.36, 4.54 and 418.70 U/g substrates for endoglucanase (CMCase), exoglucanase (FPase), β-glucosidase and xylanase respectively. The crude cellulases and xylanase required acidic condition to retain their optimum activities (pH 4.0). Crude cellulases and xylanase were more stable at 40°C compared to their optimum activities conditions (60°C for FPase and 70°C for CMCase, β-glucosidase and xylanase). SDS-PAGE and zymogram analysis showed that Aspergillus fumigatus SK1 could secrete cellulases (endoglucanase, exoglucanase and β-glucosidase), xylanase and protease. Enzymatic degradation of alkaline treated OPT with concentrated crude cellulases and xylanases resulted in producing polyoses.